Empathy and psychopathic traits as predictors of selection into business or psychology disciplines - Litten, Verity; Roberts, Lynne; Ladyshewsky, Rick; Castell, Emily; Kane, Robert (Wiley-Blackwell, 2019)
Objective: The attraction, selection, and attrition model posits that individuals actively self‐select into vocational and educational environments based on their personality traits and values. The present study investigated whether pre‐existing empathy and psychopathic personality trait differences in newly enrolled first year undergraduate students predicted selection into psychology and business vocational pathways respectively. Method: An online self‐report survey collected data on levels of psychopathic traits and empathy from 380 newly enrolled first year business and psychology undergraduate students to examine whether these pre‐existing personality traits could predict academic discipline attraction and selection. Results: Binary logistic regression analysis partially supported the proposed hypotheses. Cognitive empathy, gender, and social desirability scores were found to be significant predictors of student discipline, with females, those with higher cognitive empathy and lower social desirability scores more likely to be attracted and selected into a psychology rather than a business degree. Small to moderate effect size differences were observed, with psychology students reporting significantly higher cognitive empathy (d = 0.53) and lower interpersonal psychopathy (d = 0.27) than business students. Conclusions: Findings highlight specific personality trait differences present between newly enrolled business and psychology students and the importance of these pre‐existing differences in student vocational decision‐making. It is anticipated that findings may assist vocational and career counsellors in guiding prospective students in the direction of a vocational pathway that is best suited to their personality, as this is likely to result in increased student satisfaction and self‐esteem whilst reducing student attrition.